2019
DOI: 10.6061/clinics/2019/e1186
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Floseal® and Tranexamic Acid for Bleeding Control after Total Knee Arthroplasty: a Prospective Randomized Study

Abstract: OBJECTIVE:Tranexamic acid (TXA) and the hemostatic agent Floseal® have already been used to minimize bleeding during total knee arthroplasty (TKA).METHODS:We conducted a prospective, randomized study of 90 patients with indications for TKA. Following inclusion, the participants were randomly allocated in blocks to the following 3 groups: control, Floseal® and TXA. Bleeding parameters, including decreases in hemoglobin (Hb), drain output, number of blood transfusions and complications, were assessed. ClinicalTr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Overall, 9,067 patients received TXA while 6,592 were included in the control groups. With regard to the type of surgery, 82 studies [ 21 24 , 26 28 , 30 , 31 , 34 38 , 40 , 45 , 47 , 49 51 , 55 58 , 60 , 61 , 63 , 65 , 66 , 70 , 72 , 73 , 75 , 76 , 78 – 82 , 84 , 85 , 87 , 88 , 90 , 92 , 93 , 96 , 98 , 99 , 104 111 , 113 , 114 , 117 119 , 121 , 123 , 124 , 126 – 128 , 130 , 134 137 , 140 142 , 146 , 147 , 151 , 153 , 154 , 156 ] (5,267 cases and 3,498 controls) were focused on TKA, 41 studies [ 11 , 12 , 25 , 32 , 33 , 42 44 , 48 , 52 54 , 62 , 64 , 67 …”
Section: Resultsmentioning
confidence: 99%
“…Overall, 9,067 patients received TXA while 6,592 were included in the control groups. With regard to the type of surgery, 82 studies [ 21 24 , 26 28 , 30 , 31 , 34 38 , 40 , 45 , 47 , 49 51 , 55 58 , 60 , 61 , 63 , 65 , 66 , 70 , 72 , 73 , 75 , 76 , 78 – 82 , 84 , 85 , 87 , 88 , 90 , 92 , 93 , 96 , 98 , 99 , 104 111 , 113 , 114 , 117 119 , 121 , 123 , 124 , 126 – 128 , 130 , 134 137 , 140 142 , 146 , 147 , 151 , 153 , 154 , 156 ] (5,267 cases and 3,498 controls) were focused on TKA, 41 studies [ 11 , 12 , 25 , 32 , 33 , 42 44 , 48 , 52 54 , 62 , 64 , 67 …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, studies have confirmed that topical use of TXA can obtain similar clinical effects as intravenous use of TXA, and the less possibility of complications [20,21]. In addition, other studies have pointed out that the topical use of the hemostatic agent, such as Floseal®, has achieved significant results in controlling blood loss during TKA [22][23][24][25]. In the present study, in order to reduce the related complications caused by blood loss, all of our patients have combined intravenous and topical use of TXA.…”
Section: Discussionmentioning
confidence: 84%
“…In a study, Helito et al 23 compared IV TXA, topical hemostatic agents, and placebo; and reported that TXA had results comparable to those of topical hemostatic agents in terms of postoperative Hb reduction, and TXA was associated with less blood loss compared with placebo.…”
Section: Discussionmentioning
confidence: 99%